Characterization of lipid bilayer phases by confocal microscopy and fluorescence correlation spectroscopy - Korlach, Jonas (The National Academy of Sciences, 1999)
We report the application of confocal imaging and fluorescence correlation spectroscopy (FCS) to characterize chemically well-defined lipid bilayer models for biomembranes. Giant unilamellar vesicles of dilauroyl phosphatidylcholine/dipalmitoyl phosphatidylcholine (DLPC/DPPC)/cholesterol were imaged by confocal fluorescence microscopy with two fluorescent probes, 1,1′-dieicosanyl-3,3,3′,3′-tetramethylindocarbocyanine perchlorate (DiI-C(20)) and 2-(4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-s-indacene-3-pentanoyl)-1-hexadecanoyl-sn-glycero-3-phosphocholine (Bodipy-PC). Phase separation was visualized by differential probe partition into the coexisting phases. Three-dimensional image reconstructions of confocal z-scans through giant unilamellar vesicles reveal the anisotropic morphology of coexisting phase domains on the surface of these vesicles with full two-dimensional resolution. This method demonstrates by direct visualization the exact superposition of like phase domains in apposing monolayers, thus answering a long-standing open question. Cholesterol was found to induce a marked change in the phase boundary shapes of the coexisting phase domains. To further characterize the phases, the translational diffusion coefficient, D(T), of the DiI-C(20) was measured by FCS. D(T) values at ∼25°C ranged from ∼ 3 × 10(−8) cm(2)/s in the fluid phase, to ∼ 2 × 10(−9) cm(2)/s in high-cholesterol-content phases, to ∼ 2 × 10(−10) cm(2)/s in the spatially ordered phases that coexist with fluid phases. In favorable cases, FCS could distinguish two different values of D(T) in a region of two-phase coexistence on a single vesicle.